Non-compliance with child support obligations by application of the principle of opportunity and violation of the right of the child, case in a peruvian province - Tejada Vélez, Cristina Ruth (2021)
The objective of the research was to establish whether the non-fulfillment of the child support obligation by the application of the principle of opportunity violates the right of the child support provider to have an adequate standard of living for his or her full development in a Peruvian province. For this purpose, a non-experimental research of cross-sectional design, at a relational level, was developed. The sample consisted of 275 files, all of which were processed for omission of family assistance under the criminal type of non-compliance with child support obligations, typified in article 149 of the Penal Code. In order to collect the research data, the documentary analysis technique was used and the instrument used was a data collection form. It was found that 49.09% of the files showed debts of between 16 and 20 months of unpaid alimony, 29.09% of the accused had a debt of between S/2,001 Soles and S/4,000 Soles; and in 75.27% the full payment was not made within a reasonable period, considering the needs of the alimony payers. Finally, it was established that in 82% of the processes analyzed, the child's right to an adequate standard of living was violated, preventing him/her from achieving his/her full development. The investigation concluded that the failure to comply with the child support obligation due to the application of the principle of opportunity violates the right of the child support provider (p: 0.000).